An object-oriented programming framework for boundary integral equation methods - Marczak, R.J.
This work presents an object-oriented numerical framework for the development of computer programs based on the boundary element method (BEM). The proposed design provides a large set of classes developed specially to handle those entities most commonly found in BEM solution procedures. The framework is divided into three basic sets of classes that enable the analyst to build the code accordingly to the type of problem to be solved. The design also allows the use of an arbitrary number of subregions, which are connected automatically by imposing compatibility conditions on the interfaces. Code fragments illustrate how the use of the proposed framework can simplify the development cycle of research software based on the BEM.
Keywords: OBJECT-ORIENTED PROGRAMMING; BOUNDARY ELEMENT METHOD; SUBREGIONS; FINITE ELEMENT METHOD; ENGINEERING SOFTWARE